PIMECROLIMUS (1% CREAM) IN TREATMENT OF ATOPIC DERMATITIS AMONG CHILDREN: EFFICIENCY AND SAFETY - L.M. Ogorodova; I.A. Deev; E.S. Kulikov; E.V. Deeva (Union of pediatricians of Russia, 2007)
The main objective for treatment of atopic dermatitis is to achieve the full control. Despite the fact that control fundamentals for treatment of atopic dermatitis among children are implemented in the clinical practice, it's practically impossible as of now to deem the control of a disease as satisfactory. Such a situation is due to two main reasons: for one thing, in 37,4% of cases the severity of a disease is incorrectly assessed, which entails the prescription of a therapy that is inadequate to the degree of clinical presentations; secondly, among both doctors and patients there is still a glucocorticoidophobia, which leads to application of medications with low efficiency profile in therapy and then due to no control of atopic deramatitis it justifies the necessity to prescribe peroral glucoacorticoids. in this respect, application of calcineurin inhibitors (pimecrolimus 1% cream - elidel) as a basic therapy may be a real solution to this problem for the children, suffering from mild and moderate atopic dermatitis, to achieve the longaterm control over the disease symptoms.Key words: atopic dermatitis, children, pimecrolimus, treatment, efficiency, safety.